HUBUNGAN KONSUMEN ETNOSENTRISME DENGAN PERCEIVED QUALITY TERHADAP PRODUK LOKAL PADA USIA DEWASA MUDA DI JAKARTA - Tifany Tifany; Clara Moningka (Universitas Bunda Mulia, 2015)
The purpose of this research is to identify whether there is a correlation between consumer ethnocentrism with perceived quality of local product in Jakarta. This research background is to support the government program” Aku Cinta Indonesia (ACI)”. This program was designed to support local products as a major component that would increasethe economic development. This research is using a quantitative approach that can be defined as the measurement based on variables to obtain the statistical analysis and interpretation to a conclusion. This research is correlational research; to see whether there is a correlation between two variables. The instruments used for research were questionnaire and question form. 250 subject participate in this research and all of them are Indonesian citizen that lived in Jakarta and have already considered mature or aged above 18. The results of this research shows that there is a correlation between perceived quality of the local product and consumer ethnocentrism. The correlation between two variables is positive (r = 0,389). The results of regression between consumer ethnocentrism and perceived quality of local product is 22,7%. Based on the results obtained that there is a correlation between two variables, can be influenced by educational level, gender, income, and others. The advice for the next research is to compare it with another area or city or increasing the sample size, with more controlled variables. Keywords : perceived quality, consumer ethnocentrism, quantitative research